Scapular force: Couple ratios in healthy shoulders - An observational study reflecting typical values - Sonia Briel; Benita Olivier; Witness Mudzi (AOSIS, 2022)
Background: Scapular stability is primarily maintained through the action of the scapular stabilisers and not through bony stability. The values of the force couple ratios of the scapular stabilisers remain largely unknown. Objectives: To determine typical scapular force couple strength ratios in the pain-free shoulders of healthy female and male participants. Methods: This was a quantitative cross-sectional study. The muscle strength of the serratus anterior upper and lower fibres, the upper, middle and lower trapezius and the rhomboids (in both shoulders) were determined in kilogram force (kgf) using a handheld dynamometer. The ratios of the force couples of the scapulae of both shoulders of the participants were calculated. Participants (both female and male) with healthy shoulders were recruited from the general public (a local university, schools, church groups and sport clubs). We mainly utilised descriptive analysis. Statistical significance was set at 5%. Results: Force couple ratios were as follows (means, with SD). Dominant arm in women: upper trapezius:lower trapezius 3.63 (0.97); serratus anterior lower fibres:lower trapezius = 1.97 (0.27); middle trapezius:serratus anterior upper fibres = 0.40 (0.10); serratus anterior lower fibres:rhomboids = 1.41 (0.21); lower trapezius:rhomboids = 0.74 (0.17). Dominant arm in men: upper trapezius:lower trapezius = 2.70 (0.72); serratus anterior lower fibres:lower trapezius = 2.15 (0.45); middle trapezius:serratus anterior upper fibres = 0.47 (0.12); serratus anterior lower fibres:rhomboids = 1.40 (0.31) and lower trapezius:rhomboids = 0.17 (0.6). Conclusion: Specific force couple strength ratios were determined, between and within the nondominant and the dominant arms of the shoulders of healthy women and men. Clinical implications: Scapular stability is mainly maintained through the optimal force couple balance of the scapular stabilisers.